The distribution and potential prognostic value of SMAD protein expression in chronic lymphocytic leukemia - Magdalena Witkowska; Agata Majchrzak; Barbara Cebula-Obrzut; Ewa Wawrzyniak; Tadeusz Robak; Piotr Smolewski (Tumor Biology)
The SMAD proteins are responsible for transducing signals from activated transforming growth factor-beta. This is the first study assessing the expression of SMAD-1/8, SMAD-2/3, SMAD-4, and SMAD-7 in chronic lymphocytic leukemia cells with regard to their clinical significance and potential prognostic value. Overexpression of SMAD-1/8 was observed in 160 chronic lymphocytic leukemia patients compared to 42 healthy volunteers (p = 0.023) and was associated with a more progressive course of the disease (p = 0.016). Moreover, the high expression of SMAD-1/8 correlated with other, well-established prognostic factors, including clinical stage (p = 0.010) and lymphocyte doubling time (p = 0.021). The expression of SMAD-4 was lower in chronic lymphocytic leukemia patients compared with the control group (p = 0.003). Importantly, lower SMAD-4 levels correlated with longer progression-free survival (p = 0.009), progressive course of the disease (p = 0.002), advanced clinical stage (p = 0.0004), elevated beta-2-microglobulin and lactate dehydrogenase levels (p < 0.05), shorter lymphocyte doubling time (p = 0.009), and CD38 antigen expression (p = 0.039). In addition, lower SMAD-4 expression correlated with lower apoptotic index (p = 0.0007) and lower expression of receptors for vascular endothelial growth factors VEGFR-1 and VEGFR-2. A significant association was found between the low expression of inhibitory protein SMAD-7 and both zeta-chain-associated protein kinase 70–negative cells (p = 0.04) and lower apoptotic index (p = 0.004). No differences were observed in SMAD-2/3 expression. In conclusion, our results demonstrate a significant correlation between greater SMAD-1/8 and lower SMAD-4 expression in chronic lymphocytic leukemia cells, as well as more progressive outcome and poor prognosis. These data provide supporting evidence that the expression of SMAD proteins plays an important role in disease development and may be considered as a novel, biologic prognostic factor in this disease.